2019
DOI: 10.1186/s12935-019-0816-z
|View full text |Cite
|
Sign up to set email alerts
|

OTU deubiquitinase 4 is silenced and radiosensitizes non-small cell lung cancer cells via inhibiting DNA repair

Abstract: Background Radiotherapy is becoming one major therapeutics for non-small cell lung cancer (NSCLC). Identifying novel radiosensitizers will greatly increase the efficacy of radiotherapy and benefit more patients. OTU deubiquitinase 4 (OTUD4) has been reported involved in DNA damage repair pathways and could be a potential target for chemotherapy therapy. This study aimed to investigate the roles of OTUD4 in regulation of radiosensitivity of NSCLC via modulating DNA repair. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…This indicated that miR-494-3p targeted down-regulated the expression of OTUD4. OTUD4 has been found to be lowly expressed in non-small cell lung cancer and was able to inhibit the proliferation of cancer cells 28 . In addition, alkylation damage which is critical for cancer chemotherapy can be regulated by OTUD4 29 , but the mechanism of OTUD4 in breast cancer has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that miR-494-3p targeted down-regulated the expression of OTUD4. OTUD4 has been found to be lowly expressed in non-small cell lung cancer and was able to inhibit the proliferation of cancer cells 28 . In addition, alkylation damage which is critical for cancer chemotherapy can be regulated by OTUD4 29 , but the mechanism of OTUD4 in breast cancer has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…At present, with the development of high-throughput technology and the deepening of molecular targeting technology research, in addition to these traditional predictors, abnormal epigenetic molecular markers, such as DNA methylation and noncoding RNA, can also be used for prognosis prediction. Wu et al [81] showed that OTUD4 (OTU deubiquitinase 4) is silenced by promoter methylation and that its downregulation correlates with poor prognosis in NSCLC. Li et al [82] found that four methylation-driven genes, GCSAM, GPR75, NHLRC1, and TRIM58, could serve as prognostic indicators for LUSC.…”
Section: 52mentioning
confidence: 99%
“…Radiotherapy is one of the main treatments used in the management of advanced non‐small cell lung cancer (NSCLC) . During radiotherapy, ionizing radiation rays destroy the DNA of tumor cells, thereby suppressing their proliferation and inducing their apoptosis . Unfortunately, multiple factors lead to radiation resistance in tumor cells, while the increase in the radiation dose will also increase the risk of radiotherapy‐related complications, such as radiation pneumonitis and radiation pulmonary fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 During radiotherapy, ionizing radiation rays destroy the DNA of tumor cells, thereby suppressing their proliferation and inducing their apoptosis. 3 Abbreviations: 3'-UTR, 3'-untranslated region; DMEM, Dulbecco modified Eagles' medium; FBS, fetal bovine serum; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; miR-NC, miRNA negative control; miRNAs/miRs, microRNAs; NSCLC, non-small cell lung cancer cells; PI, propidium iodide; qRT-PCR, quantitative real-time PCR; WEE1, WEE1 G2 checkpoint kinase.…”
Section: Introductionmentioning
confidence: 99%